PENGARUH LOKASI DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN PADA CAFE TITIK KUMPUL CAPORE SITUBONDO DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Purba, Sherly Septian Diana; Kusnadi, Edy; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Location refers to various marketing activities that have facilitated and facilitated the delivery or distribution of goods and services from producers to consumers. Service quality is something intangible provided by the service provider to its customers who are then compared the differences between the reality and the expectations they receive from the service. A consumer is said to be loyal or loyal if the consumer shows buying behavior on a regular basis or there is a condition where it requires consumers to buy at least twice in a certain time interval. In general, customer expectations are estimates or customer beliefs about what will be received when they use services with good or satisfactory service. Satisfaction or dissatisfaction of consumers is part of the consumer experience of a product or service offered. The purpose of this study was to analyze and examine the effect of Location and Service Quality on Consumer Loyalty at the Gathering Point Cafe, Capore Situbondo with Consumer Satisfaction.. This study uses a probability sampling technique with random sampling (simple random sampling). Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that location has a positive but not significant effect on consumer satisfaction, service quality has a significant positive effect on consumer satisfaction, location has a significant positive effect on consumer loyalty, service quality has a significant positive effect on consumer loyalty, Consumer satisfaction has a positive significant effect on consumer loyalty, location on consumer loyalty through consumer satisfaction has a positive but not significant effect, service quality on consumer loyalty through consumer satisfaction has a significant positive effect.